2002
DOI: 10.1053/ejvs.2002.1647
|View full text |Cite
|
Sign up to set email alerts
|

Areas of Concern, Quality of Life and Life Satisfaction in Patients with Peripheral Vascular Disease

Abstract: for a full understanding of how peripheral vascular disease affects the individual, disease specific questions need to be added to generic QOL instruments and measurements of life satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 34 publications
0
36
0
2
Order By: Relevance
“…Other studies have shown similar results from interviews with patients with PAD, i.e. feelings of isolation and fear of loss of function and independence (Hallin et al, 2002;Treat-Jacobson et al, 2002). However, extensive effect on social life and emotional impact has not commonly been documented in the literature.…”
Section: Discussion Of the Findingsmentioning
confidence: 67%
“…Other studies have shown similar results from interviews with patients with PAD, i.e. feelings of isolation and fear of loss of function and independence (Hallin et al, 2002;Treat-Jacobson et al, 2002). However, extensive effect on social life and emotional impact has not commonly been documented in the literature.…”
Section: Discussion Of the Findingsmentioning
confidence: 67%
“…To date, most previous studies have focused on the impact of PAD on these psychosocial outcomes, not on the role of psychosocial characteristics as risk factors for PAD. [11][12][13][14][15][16] In this study, we hypothesized that individuals with high levels of anger proneness and depression and low levels of social support would be at an increased risk for PAD, as reflected by a low ankle-brachial index (ABI), leg revascularization procedures, or intermittent claudication.…”
mentioning
confidence: 99%
“…In a more age, gender and co-morbidity matched historical control group of patients who had undergone open repair for abdominal aortic aneurysm without suffering from SCI, life satisfaction evaluation by LiSat-11 showed that sexual functioning and psychological health were the domains that were most suppressed, whereas the other domains appeared to be very little affected. 26 In the present study, there were three patients suffering from pre-and perioperative stroke, which could have influenced their life satisfaction. Indeed, life satisfaction scores have been shown to be significantly impaired in stroke survivors compared with healthy controls.…”
Section: Discussionmentioning
confidence: 80%